Repair versus nonrepair of medial meniscus posterior root tear: A systematic review of patients' selection criteria, including clinical and radiographic outcomes. Issue 10 (March 2020) - Lee, Jin Kyu; Jung, Min; Yang, Jae Hyuk; Song, Si Young; Shin, Young-Soo; Cha, Myoungsoo; Jung, Dawoon; Seo, Young-Jin
Abstract: Background: The general consensus regarding a rational choice among various treatment strategies for medial meniscus posterior root tears (MMPRTs) has yet to be clearly established. The purpose of this systematic review was to analyze patient selection criteria based on index arthrosis, as well as clinical and radiological outcomes after repair or nonrepair treatment in patients with MMPRTs. Methods: A systematic electronic search was performed with established medical databases. Data from the selected studies which were assessed using the modified Coleman methodology score were analyzed in terms of index arthrosis and degree of lower limb alignment, functional and radiologic outcomes after meniscus repair, partial meniscectomy, and conservative treatment. Results: In total, 17 studies and 655 patients (665 cases) were enrolled in this study, of which 42% (279 cases) underwent MMPRT repair and 58% (386 cases) were treated using a nonrepair strategy. The mean age and the mean follow-up period were 54.7 years and 32.5 months in the repair group, respectively, and 57.0 years and 49.3 months in the nonrepair group, respectively. Based on the clinical data available in this study, most of the MMPRT repairs were performed in patients with mild arthrosis, mild varus alignment, and mild chondral injury. Although data were limited, the percentage of patients with mild chondral injury was only 40% in the nonrepair group, implying that the nonrepair group may have more advanced arthrosis at the baseline. Based on the available Lysholm score across the studies, good functional outcomes were obtained in the repair group, whereas the results of the nonrepair treatment exhibited fair functional outcomes that were somewhat heterogenous. The radiologic outcomes of the mean 5 years' follow-up study showed that arthritic change could not be prevented by either nonrepair or repair treatment. Conclusions: In general, MMPRT repair led to significant improvement in clinical outcomes. On the contrary, the nonrepair group also showed symptomatic relief in some selected cases, despite the somewhat heterogenous results. Given the subgroup analysis for the functional results reported in this review, strict patient selection is important to obtain satisfactory clinical outcomes, regardless of the treatment option selected.